Literature Review: Mekanisme Bacterial Vaginosis dalam Infeksi Intrauterin dan Dampaknya terhadap Kesehatan Reproduksi Wanita - Ayuningtyas, Diah; Dewi Puspita Sari , Ratna; Sutarto; TA Larasati (CV. Jasa Sukses Abadi, 2024)
Intrauterine infection is an inflammatory condition involving various components of pregnancy, including the amniotic fluid, placenta, fetus, amniotic membranes, and decidua. One of the main mechanisms contributing to this infection is ascending infection from the lower genital tract, in which microorganisms such as Ureaplasma, Escherichia coli, and Streptococcus agalactiae ascend into the amniotic cavity. Imbalances in the vaginal microbiota, such as in bacterial vaginosis (BV), exacerbate the risk of ascending infection, by replacing the protective Lactobacillus dominance with anaerobic pathogens. This condition can lead to various obstetric complications, including preterm labor, preterm rupture of membranes, and increased maternal and neonatal morbidity and mortality. Studies have shown that changes in the vaginal microbiota can have significant impacts on reproductive health. Processes such as menstruation, sexual activity, and invasive medical interventions can alter the composition of the microbiota, affect vaginal pH, and reduce the dominance of Lactobacillus, thereby increasing the risk of intrauterine infection. In addition, uterine pumps play a role in the transfer of microorganisms from the vagina to the uterine cavity, further increasing the risk of infection. With the advancement of molecular technology, the understanding of vaginal and uterine microbiota is growing, especially in relation to the mechanism of intrauterine infection. Microbiota imbalance not only contributes to inflammation, but also alters immunological signaling pathways, reduces the barrier function of the endometrial epithelium, and allows pathogens to cross the placenta. Therefore, microbiota-based approaches, such as the use of Lactobacillus probiotics, as well as education about reproductive health, are potential strategies in preventing complications associated with intrauterine infection.